Rolêzicho: um projeto de multiletramentos em contexto de fronteira no oeste do Paraná e a formação ampliada do professor de língua espanhola no período pandêmico - Paiva, Tatiane Lima de (2022)
The general objective of this thesis is to reflect on the teaching experience, in a multiliteracies project with a view to the expanded training of spanish teachers in the context of borders, more specifically in the western region of the state of Paraná, focusing on linguistic policies and the (im)possibilities of emergency remote teaching within the scope of Covid-19. Thus, the specific objectives are: (1) to analyze the linguistic policies aimed at teaching spanish in Brazil and in the state of Paraná; (2) to describe extended training practices for spanish teachers in a multiliteracies project from the perspective of translanguages, during a pandemic period, in a border context; (3) highlight the challenges and (im)possibilities of emergency remote teaching in the expanded training of spanish teachers. In line with the objectives, the research question of this work is: how can a multiliteracies project, developed via emergency remote teaching, contribute to the expanded training of the spanish teacher, in a cross-border context? With these objectives and research question, the thesis is defended that a teaching experience based on multiliteracies can contribute to an expanded training of spanish teachers, to work in the context of borders in the western region of Paraná. The ongoing discussion about multiliteracies added to the expanded training of spanish teachers is justified for different purposes: permanent reflection on the practice itself as a teacher-trainer; to contribute to the promotion of research on multiliteracies projects connected to the teaching and learning of the spanish language; encourage teachers and students to use the spanish language through multiliteracies, contributing to the quality of initial and continuing teacher training. The theoreticalmethodological approach used to generate and analyze data is situated in the area of Applied Linguistics, based on the qualitative research methodology with an interpretive basis, allied to collaborative critical action research. The data generated were obtained through participant observation, field diary, document analysis, application of individual online interviews and recording and transcription of group discussion with students from different years of the Spanish Letters course at Universidade Estadual do Oeste do Paraná, campus of Marechal Cândido Rondon, participants in the teaching project. The results obtained from the data analysis demonstrate that the teaching project contributed to an expanded training, by providing: (1) reception in relation to peers; (2) sensitivity to cultural, social and linguistic diversity and plurality; (3) intercomprehension; (4) translingual practices; (5) use of technology in education; (6) reflections on points to be rethought for future projects.